Lateralization value of functional movement rating in volleyball players` injury prevention - Piech, J.; Bajorek, W.; Plonka, A.; Kuchciak, M.; Bobula, G. (Journal of Physical Education and Sport, 2020)
The Game variability and asymmetry of volleyball movements often lead to overloads affecting the mobility system. Premature specialization limits versatility and motor preparation, which increases the risk of injury. Therefore, systematic comprehensive control becomes very important. Functional Movement Screen (FMS) is one of the tools used for the functional assessment of an athlete. The Functional Movement Screen (FMS) test applied in the presented research allows assessment of players' movement abilities as well as assessing their susceptibility to injury which can be caused by asymmetry volleyball. The set of preformed activities in the test is based on global movement patterns, it is used in both physiotherapy and sports. A revision of scientific research confirms the high repetitiveness of this research tool (ICC = 0,98) while being applied to functional assessment of sportspeople. The aim of the study was to assess the influence of lateralization of functional muscle efficiency of volleyball players in the first league. The FMS test allows one to determine the motor skills of a player and check his susceptibility to injury due to asymmetry appearing in this sport. The research showed a number of irregularities in movement patterns in the group of volleyball players. More than half of the assessed sportspeople gained less than 18 points in the FMS test, which shows the presence of additional compensation movement during the test. The predisposition for higher injury risk within volleyball players may be a consequence of the fact. The largest disorders during the tests were observed during by the SM test (1.9/3), while the smallest disorders during the ASLR test (2.6/3 and 2.7/3). The average score obtained by players practising professional volleyball was 16.5/21 points. The lowest average result was obtained in the shoulder mobility test. Some players felt pain during the test which prevented them from performing the task correctly. According to FMS assumptions, a result between 18-14 points suggests the presence of certain motor disorders that increase the incidence of injury by about 25-35%. Disproportions that occur in the subjects are caused by greater exploitation of a given muscle group. In the case of volleyball players, a slight asymmetry in the individual trials of FMS has also been observed. Asymmetry often leads to muscular dystonia which can cause serious injury. Asymmetry was observed in the majority of players in the research.